2017
DOI: 10.1371/journal.pone.0172909
|View full text |Cite
|
Sign up to set email alerts
|

Supplementation of cow milk naturally enriched in polyunsaturated fatty acids and polyphenols to growing rats

Abstract: This study investigated whether intake of cow milk, naturally enriched with polyunsaturated fatty acids (PUFA, omega-3) and polyphenols (from propolis extract and vitamin E), from manipulation of cow’s diet, would result in positive metabolic effects in rats from weaning until adulthood. Male Wistar rats were fed a standard chow diet or a hypercaloric diet (metabolically disturbed rats, obese) which was supplemented with either whole common milk, milk enriched with PUFA (PUFA-M) or milk enriched with PUFA and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 39 publications
0
17
0
Order By: Relevance
“…Other similar studies in the diabetic animal model were not found in the literature [ 18 ]. Thus, we could verify that supplementing the diets of dairy cows with PUFA-rich oil and polyphenols transfers part of these compounds into milk.…”
Section: Discussionmentioning
confidence: 92%
See 4 more Smart Citations
“…Other similar studies in the diabetic animal model were not found in the literature [ 18 ]. Thus, we could verify that supplementing the diets of dairy cows with PUFA-rich oil and polyphenols transfers part of these compounds into milk.…”
Section: Discussionmentioning
confidence: 92%
“… 1 Milk composition reported by Santos et al [ 18 ]. Data are mean ± standard deviation from a single sample for each treatment.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations